Fenomen wielkich wystaw – przekaz pokoleń i wyraz kultury historycznej swoich czasów - Julkowska, Violetta (Historyka Studia Metodologiczne, 2023)
The aim of the article is to reflect on the phenomenon of great art exhibitions, gathering exhibits, mainly paintings, exceptional from the perspective of national cultural heritage, which collectively represent a defined generational message. The reflection included the best‑known exhibitions of recent decades, being an expression of the historical culture of a time of great changes in the life of Polish society at the turn of the 21st century. These are two exhibitions at the National Museum in Kraków, the first exhibition ever by Marek Rostworowski, “Polish self‑portrait” (1979); the second is an exhibition of Marek Szczerski’s work entitled #dziedzictwo/heritage (2017); a jubilee exhibition organised by the National Museum in Warsaw in collaboration with the Louvre‑Lens Museum, the National Museum in Poznan and the Adam Mickiewicz Institute on the centennial of regaining independence, entitled “Poland. The power of the image” (2019‑2021). This reflection also includes the monumental exhibition organised collectively by the Royal Castle in Warsaw and the Martin Gropius Bau in Berlin, with the participation of the curator Anda Rottenberg, entitled “Side by side. Germany‑Poland 1000 years of history in art.” (2012).
Keywords: wystawy malarstwa; kultura historyczna; dziedzictwo narodowe; pamięć kulturowa; artystyczna reprezentacja przeszłości